UI/UX Analysis on the Geek Studio Website Using the User Centered Design and User Experience Questionnaire (UEQ) Method - Fitriana, Gita Fadila; Rahadian, Reva (IPTEK The Journal for Technology and Science, 2023)
GEEK STUDIO engaged in photography such as photo studios and rental shooting tools. Based on the results of an interview with the owner of GEEK STUDIO, there is a problem to develop a website profile system that cannot be used optimally because the existing website is still considered less than optimal in terms of user experience (UX) and user interface (UI) so it is less attractive and less comfortable to use. therefore, the researcher will analyze the website which according to the source is still the maximum turning using the UCD and UEQ methods. User-Centered Design (UCD) is one of several design methods where the method is focused on the needs and preferences of its users. UCD is a process that is carried out repeatedly where the design and evaluation are developed from the initial stage to the implementation periodically. Then the User Experience Questionnaire (UEQ) is a method in the form of a questionnaire where the method serves to measure the viewing experience of users of a product. The most basic goal of UEQ is to quickly calculate its user experience through questionnaires. Based on research data that has been carried out by the author, a conclusion can be drawn where the results of the study have produced previous design benchmark values, namely attractiveness 1.11, perspicuity 1.16, efficiency 1.41, dependability 1.31, stimulation -0.76 and novelty -0.96 While in the design afterward, namely attractiveness 2.49, perspicuity 2.20, efficiency 2,26, dependability 2.00, stimulation 2.05 and novelty 2.18, Based on this, it can be seen the improvement of the chart from the benchmark which was originally from bad to above average to excellent overall.